Multifractal analysis of meat-analog based coated fried foods texture profile - Bhuiyan, Md. Hafizur Rahman; Yeasmen, Nushrat; Ngadi, Michael O. (Food Structure, 2024)
Texture profile of meat-analog (MA) based fried food products is a complex structure, and rarely studied subject. MA-based fried products mechanical-texture-profile were considered as “fractal geometry” to characterize their textural properties by employing complex statistical approach namely multifractal analysis (MFA). Wheat and rice flour-based batter systems were used to coat the MA, and were fried (at 180 °C) for 2, 4, and 6 min in canola oil. Instrumental puncture test was employed to get mechanical-texture-profile of MA-based fried products and obtained profile was evaluated by MFA. Results revealed that batter-formulation and frying time (FT) impacts the evolution of textural attributes (hardness, brittleness, crispiness), moisture-fat profile and microstructural properties of MA-based coated fried product. The MFA outcomes (Singularity spectra & Rényi spectra) depicts that breakage structure (force distribution) of studied MA-based fried products are non-homogeneous and possesses multifractal scaling behavior. Higher heterogeneity of force distribution is observed in lower concentration of force at outer-crust region compared to inner-core region of coated MA. Heterogeneity of force distribution are positively correlated with FT. Batter-formulation showed substantial impact on texture-profile of MA-based coated fried products and consequently influenced the obtained multifractal parameters. Principal component analysis (PCA) reveals varying extent of correlation between moisture-fat, textural attribute, microporosity and selected multifractal parameters (Δα, Δfα, R-L, ΔD) of fried MA. Complex structural pattern of batter coated fried meat-analog (MA)s mechanical texture profile have been successfully and statistically characterized by employing multifractal analysis. This study unraveled the interdependencies among batter-formulation, frying process, mass-profile, microstructure, textural attributes and multifractal parameters. Findings of this study could be used to customize textural attributes of the low fat-containing fried foods. Overall, this work will serve as a ground for designing the production process of emerging MA-based batter-coated fried product. [Display omitted] •Batter formulation and frying time controls moisture-fat profile, textural traits and microstructure of meat-analog (MA) based fried foods.•Mechanical texture profile of fried MA-based coated products are Multifractal geometry.•Multifractal analysis (MFA) shows heterogeneous force distribution results hard, brittle and crispy texture in MA-based coated fried food.•Batter formulation and/or frying time can offer desired textural traits in MA-based coated fried food.